2017
DOI: 10.1016/j.energy.2017.01.101
|View full text |Cite
|
Sign up to set email alerts
|

Battery capacity and recharging needs for electric buses in city transit service

Abstract: This paper evaluates the energy consumption and battery performance of city transit electric buses operating on real day-today routes and standardized bus drive cycles, based on a developed framework tool that links bus electrification feasibility with real-world vehicle performance, city transit bus service reliability, battery sizing and charging infrastructure. The impacts of battery capacity combined with regular and ultrafast charging over different routes have been analyzed in terms of the ability to mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(128 citation statements)
references
References 23 publications
2
118
1
7
Order By: Relevance
“…Gao et al estimated the power of auxiliary systems on series and parallel hybrid buses as being 2.29 kW [50], with 3.75 kW for electric buses [51], as opposed to Göhlich et al, who found power consumption of 6 kW for the auxiliary systems [52].…”
Section: Vehicle Transmissionmentioning
confidence: 97%
“…Gao et al estimated the power of auxiliary systems on series and parallel hybrid buses as being 2.29 kW [50], with 3.75 kW for electric buses [51], as opposed to Göhlich et al, who found power consumption of 6 kW for the auxiliary systems [52].…”
Section: Vehicle Transmissionmentioning
confidence: 97%
“…Rogge et al (2015) further discussed the trade-off between passenger and battery capacity and the interdependency between charging power and battery capacity in order to electrify an existing bus network. Battery sizing is investigated in Gao et al (2017). 1 Fuel cell powered busses are not considered in this study because the cost of the required infrastructure and the current market price of hydrogen is not yet competitive.…”
Section: Figure 1: Morphological Matrix Of Available Technology Optiomentioning
confidence: 99%
“…where ηch is the BEB charging efficiency, 97% [64], GHGWTT is the WTT GHG emissions factor (gCO2e/MJ) and GHGTTW is the TTW GHG emissions factor (gCO2e/MJ) ( Table 5). For the BEB configuration, ηth = 100% in equations 8 and 9.…”
Section: Use Phase Modelmentioning
confidence: 99%
“…[73]. b Sum of clutch, gearbox, final drive and wheel efficiencies from [64]. c Traditionally in TIF studies, percentage deviations from the baseline are used, this study also includes variability of inputs applicable to BEBs only.…”
Section: Tank-to-wheels (Ttw) Analysismentioning
confidence: 99%